Fourier-Chebyshev Pseudospectral Method for Three-Dimensional Vorticity Equation (Journal of Computational Mathematics, 1998)
In this paper, a Fourier-Chebyshev pseudospectral scheme with mixed filtering is proposed for three-dimensional vorticity equation. The generalized stability and convergence are proved. The numerical results show the advantages of this method.